Monitoring the growth and stress responses of yeast cells by two-dimensional fluorescence spectroscopy: first results - Podrazký, O; Kuncová, G; Krasowska, A; Sigler, K (Folia microbiologica, 2003)
S. cerevisiae growth and responses to different treatments were monitored by two-dimensional fluorescence spectroscopy, which simultaneously detects the fluorescence of a number of cells' own fluorophores. Growth curves of cultures of free cells were measured by means of tryptophan fluorescence in nonfluorescent culture medium and a flow-through system at a suitable excitation/emission beam geometry. Fast responses of the cells to anaerobic-aerobic transition or addition of glucose, methanol or cyanide, which could not be measured in this system because of the time delay inherent in transporting the cells from the culture flask to the cuvette, were monitored with cells immobilized in alginate. The major fluorescence changes caused by these treatments belonged to NAD(P)H which is a good indicator of the redox state of the cells.
Keywords: Cells, Immobilized; methanol; Heat-Shock Response; kultivační média; Alginates; Culture Media; Glucuronic Acid; imobilizované buňky; kyselina glukuronová; Methanol; algináty; Hexuronic Acids; NADP; reakce na tepelný šok; kyseliny hexuronové; Spectrometry, Fluorescence; Saccharomyces cerevisiae; kyanid draselný; fluorescenční spektrometrie; Potassium Cyanide